2023
DOI: 10.1039/d3dd00002h
|View full text |Cite
|
Sign up to set email alerts
|

GFlowNets for AI-driven scientific discovery

Abstract: Tackling the most pressing problems for humanity, such as the climate crisis and the threat of global pandemics, requires accelerating the pace of scientific discovery. While science has traditionally relied...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…For example, Brookes et al ( 2019) built variational autoencoders (VAEs) that generate desirable designs by iteratively improving the VAE and its designs, guided by a design model. Jain et al (2022) used GFlowNets for sequence design, another class of generative models that are trained to output designs that span all modes of some design model's prediction distribution. Linder et al (2020)'s deep exploration networks (DENs) are generative models that are trained to output diverse yet desirable sequences and again use design model predictions to guide the training process.…”
Section: Offline Mbo For Designing Biological Se-mentioning
confidence: 99%
“…For example, Brookes et al ( 2019) built variational autoencoders (VAEs) that generate desirable designs by iteratively improving the VAE and its designs, guided by a design model. Jain et al (2022) used GFlowNets for sequence design, another class of generative models that are trained to output designs that span all modes of some design model's prediction distribution. Linder et al (2020)'s deep exploration networks (DENs) are generative models that are trained to output diverse yet desirable sequences and again use design model predictions to guide the training process.…”
Section: Offline Mbo For Designing Biological Se-mentioning
confidence: 99%
“…By relying on the new experimental data, only a limited number of training samples can be expected, confining the choice of ML models to those with a lower number of parameters, such as multilayer perceptrons (MLP) with as few as two layers . A recent advance in the area of active learning is the development of GFlowNets, networks designed to suggest diverse and accurate candidates in a machine–expert loop to accelerate scientific discovery. Studies using such networks have demonstrated their potential for designing small molecules; however, the utility for the design of proteins remains to be reliably demonstrated.…”
Section: Protein Engineering Tasks Solved By Machine Learningmentioning
confidence: 99%
“…The action distribution induced by this EBM in a structured action space is highly multimodal, and sampling from such a high-dimensional distribution is intractable. To this end, we introduce a recently proposed novel and powerful generative model, Generative Flow Networks (GFlowNet) [4,5,33,99], as the efficient diverse policy sampler. GFlowNet can be regarded as amortized Monte-Carlo Markov chains (MCMC), which gradually builds composable environmental actions through the single but trained generative pass of "building blocks (i.e., atomic actions)", so that the final sampled environmental actions obey a given energy-based policy distribution.…”
Section: Introductionmentioning
confidence: 99%